Role of herbal drugs on neurotransmitters for treating various CNS disorders: A review - Dubey T.; Sahu G.; Kumari S.; Yadav B.S.; Sahu A.N. (My University, 2025)
Neurotransmitters are chemical messengers in the human body and are associated with several CNS disorders. Plant drugs can be used as agonist/antagonist/modulator to neurotransmitters to treat CNS disorders like Alzheimer’s disease, Parkinson’s disease etc. The current review comprises the role of various neurotransmitters in CNS diseases and plants to treat them. This review compiles most of the scientific research related to the role of neurotransmitters and potential plants to treat various CNS disorders. Authors hope that researchers will utilize this current knowledge to explore and establish the potential herbal drugs to treat CNS disorders. This review has been compiled using references from major databases such as Chemical Abstracts, Medicinal and Aromatic Plants Abstracts, ScienceDirect, SciFinder, Google Scholar, Scopus, PubMed, Springer Link, and books, without limiting the dates of publication. General web searches were also carried out using Google and Yahoo search engines by applying some related search terms (e.g., Neurotransmitters, herbal drugs, pathophysiology and CNS disorders). The articles related to agriculture, ecology, and synthetic works and those using languages other than English or Persian have been excluded. Neurotransmitters play an important role in the pathophysiology of various CNS disorders. Plants can be used as potential drugs to treat various CNS disorders as confirmed by various pharmacological studies illustrated in this review. This review discusses the current knowledge of neurotransmitters, their role in CNS disorders and herbal drugs that can be used to treat these diseases. © 2018, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved.